Cho hàm số \(f(x)\) thỏa mãn \(f'(x)=x\mathrm{e}^x\) và \(f(0)=2\). Tính \(f(1)\).
\(f(1)=8-2\mathrm{e}\) | |
\(f(1)=\mathrm{e}\) | |
\(f(1)=3\) | |
\(f(1)=5-2\mathrm{e}\) |
Chọn phương án C.
Vì \(\displaystyle\int\limits_{0}^{1}f'(x)\mathrm{\,d}x=f(1)-f(0)\) nên $$f(1)=\displaystyle\int\limits_{0}^{1}f'(x)\mathrm{\,d}x+f(0)=3.$$
Chọn phương án C.
Đặt \(\begin{cases}
u=x\\ v'=\mathrm{e}^x
\end{cases}\Rightarrow\begin{cases}
u'=1\\ v=\mathrm{e}^x
\end{cases}\)
Bằng phương pháp từng phần ta có $$\begin{aligned}
f(x)&=\displaystyle\int f'(x)\mathrm{\,d}x=x\mathrm{e}^x-\displaystyle\int\mathrm{e}^x\mathrm{\,d}x\\
&=x\mathrm{e}^x-\mathrm{e}^x+C=(x-1)\mathrm{e}^x+C.
\end{aligned}$$
Vì \(f(0)=2\) nên \((0-1)\mathrm{e}^0+C=2\Leftrightarrow C=3\).
Vậy \(f(x)=(x-1)\mathrm{e}^x+3\).
Do đó \(f(1)=3\).